The investigation of liquid phase reaction of 4-aminotoluene with ozone in the presence of manganese bromide catalyst - Галстян, Андрій Генрійович; Керемет, Михайло Анатолійович (Technology audit and production reserves, 2015)
A new catalytic system Mn(ІІ)- KBr-H2SO4-Ас2О to obtain 4-aminobenzaldehyde treatment by ozonation of 4-aminotoluene is developed. It has been shown that injection of potassium bromide significantly increases the depth, speed and selectivity of substrate oxidation, the main reaction product is 4-acetylaminobenzylidendiacetate with the discharge of 84.5%. Active particles responsible for the inclusion of 4-aminotoluene oxidation by a methyl group in the presence of manganese (II) acetate and potassium bromide is manganese bromide radical-ion (Mn (II) Br •), which is more active than Mn (III) and because of the higher rate of initiating oxidation by a methyl group. It is proposed the mechanism of the process by which the substrate oxidation is carried out by ion-radical unchain mechanism in which manganese-bromide radical is generated mainly in reaction with ozone. The main functions of sulfuric acid in the system are determined. It affects the main stages of the catalytic cycle: reduces the rate of manganese bromide complex reaction with ozone, significantly increases the rate of substrate oxidation by a methyl group and catalyzes the acylation reaction. These data are the basis for laying the foundations of technology of 4- aminotoluene oxidation by ozone to 4-aminobenzaldehyde and development of preparative and industrial methods for obtaining of aromatic aldehydes.